2004
DOI: 10.1577/a03-010.1
|View full text |Cite
|
Sign up to set email alerts
|

Adult Recoveries of Volitionally and Forced‐Released Juvenile Coho Salmon

Abstract: Test groups of coded‐wire‐tagged yearling coho salmon Oncorhynchus kisutch were either volitionally released or forcibly released for 3 years at two hatcheries. Results for the two release methods showed similar survivals for age‐2 males (jacks) or age‐3 fish. We suggest that volitional release could have benefits in feed savings and allow limited water to be redirected in the hatchery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Evenson and Ewing (1992) even removed nonmigrating steelhead from the volitional groups so they were not counted as fish released, and adult returns were still significantly greater for forcibly released fish. Appleby et al (2004) observed similar adult return rates between the two release methods for coho salmon O. kisutch.…”
supporting
confidence: 51%
“…Evenson and Ewing (1992) even removed nonmigrating steelhead from the volitional groups so they were not counted as fish released, and adult returns were still significantly greater for forcibly released fish. Appleby et al (2004) observed similar adult return rates between the two release methods for coho salmon O. kisutch.…”
supporting
confidence: 51%
“…2011), while others have shown a significant advantage of FR (Evenson and Ewing 1992). A study conducted with Coho Salmon O. kisutch also found no significant survival advantage between FR and VR methodologies (Appleby et al 2004). However, research that has examined the survival differences between release methodologies for spring Chinook Salmon is sparse.…”
mentioning
confidence: 98%